2009
DOI: 10.2187/bss.23.131
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Cell Wall-Sustaining System in Gravity Resistance in Plants

Abstract: Gravity resistance is one of two principal gravit y re sponse s in plants , comparable to gravitropism. In the final step of gravity resistance, plants increase the rigidity of their cell walls via modifications to the metabolism. Various constituents of the plasma membrane and the cytoskeleton play an important role in sustaining functions of the cell wall in gravity resistance. Mechanoreceptors located on the plasma membrane are involved in the perception of gravity signal. The perceived signal may be, at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…12 These results suggest that cortical microtubules are involved in gravity resistance. 2,13 To confirm this point, we investigated the changes in cell morphology and orientation of cortical microtubule arrays in hypocotyls of Arabidopsis tubulin mutants grown under hypergravity conditions. 14 We used three mutants, tua3(D205N), tua4(S178∆) and tua6(A281T) 15,16 in the study.…”
Section: Involvement Of Mechanoreceptors In Gravity Resistancementioning
confidence: 96%
“…12 These results suggest that cortical microtubules are involved in gravity resistance. 2,13 To confirm this point, we investigated the changes in cell morphology and orientation of cortical microtubule arrays in hypocotyls of Arabidopsis tubulin mutants grown under hypergravity conditions. 14 We used three mutants, tua3(D205N), tua4(S178∆) and tua6(A281T) 15,16 in the study.…”
Section: Involvement Of Mechanoreceptors In Gravity Resistancementioning
confidence: 96%
“…Studies on cell wall changes under true microgravity in space have been limited to fragmental analyses of the levels and organization of cellulose and lignin, without any report on the effects of microgravity on the mechanical properties Hoson et al, 2005;Hoson et al, 2009). We have analyzed both the mechanical and chemical properties of the cell wall of space-grown seedlings under conditions where environmental factors other than gravity, such as temperature, light, water, and gas composition, were strictly regulated (Hoson et al, 2002;Soga et al, 2002).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…We have termed this response 'gravity resistance' and examined its nature and mechanism mainly by ground-based experiments using hypergravity conditions, produced by centrifugation, and by space experiments Hoson et al, 2005;Hoson et al, 2009). As a result, we have clarified the outline of the sequence of events in gravity resistance, and shown that gravity resistance is surely the major graviresponse in plants, distinct from gravitropism.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of gravity resistance consists of signal perception, transformation and transduction of the perceived signal, and response to the transduced signal, as is seen in other environmental responses as well. The outline of the sequence of events in gravity resistance has already been described [ 5 , 15 ]. The gravity signal may be perceived by mechanoreceptors (mechanosensitive ion channels) on the plasma membrane, and it appears that amyloplast sedimentation in statocytes is not directly involved.…”
Section: Mechanisms Controlling Gravity Resistancementioning
confidence: 99%